A linearized integral equation reconstruction method of admittivity distributions using Electrical Impedance Tomography. (May 2023) - Sebu, Cristiana; Amaira, Andrei; Curmi, Jeremy
Abstract: In this article, a novel reconstruction algorithm that approximates smooth complex admittivity distributions for Electrical Impedance Tomography is presented. This non-iterative algorithm is based on a linearized integral equation approach which has been extended to simultaneously reconstruct the conductivity and permittivity distributions of two-dimensional domains from boundary measurements of high-frequency alternating input currents and induced potentials. Reconstructions from noisy simulated data are obtained from single-time, time-difference and multiple-times data.